Role of nurses in a field hospital aimed at patients with Covid-19 - Claudete Aparecida Conz; Vanessa Augusta Souza Braga; Heliandra Holanda Reis; Soélen Silva; Maria Cristina Pinto de Jesus; Miriam Aparecida Barbosa Merighi (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To understand the role of nurses in field hospitals aimed at patients with Covid-19. Methods: Qualitative research based on Alfred Schütz's social phenomenology. Twenty nurses working in São Paulo were interviewed between May and June 2020. The testimonies were organized and analyzed based on the theoretical-methodological and thematic framework. Results: The following categories emerged: "Nurses' challenges in field hospital care", "Visibility of nursing in the Covid-19 pandemic scenario" and "Covid-19 post-pandemic professional valorization". Final considerations: The reflection on the results that emerged in this study may contribute to support improvements in training, working conditions and valuing nurses, considering the importance of this professional category in the scope of health services. New investigations may increase knowledge in the area, providing subsidies for professional role in this and other health situations that require nursing intensity and excellence.